Genetic differences between sexes for morphometric traits of GIFT tilapia - Reis Neto, Rafael Vilhena; Lopes de Oliveira, Carlos Antonio; Ribeiro, Ricardo Pereira; Fonseca de Freitas, Rilke Tadeu; Allaman, Ivan Bezerra; Oliveira, Sheila Nogueira de (Wiley-Blackwell, 2017)
The study was carried out to verify the genetic differences in the morphometric traits between male and female tilapia GIFT under the selection for weight gain. The data set used contained information of 6650 animals of the third (2198), fourth (1720) and fifth (2732) generations of GIFT in Brazil, in addition to the 8590 animals, of the first five generations, included in the relationship matrix. The morphometric traits used were standard length (SL: 19.8 +/- 1.7), body depth (BD: 7.6 +/- 0.76), body width (BW: 3.5 +/- 0.54), body area (BA: 151.3 +/- 27.6) and body volume (BV: 536.7 +/- 143.5). Bicharacter analyses were performed considering the same morphometric measure evaluated for each sex as different traits to estimate the (co)variance components. The heritability and environmental common effects of the larval and fry phases for each trait of each sex were estimated. Genetic correlations between males and females for the same body trait were estimated. The larval effect was higher for females (SL=0.1; BD=0.07; BW=0.05; BA=0.09; BV=0.09) than for males (SL=0.04; BD=0.03, BW=0.01, BA=0.04; BV=0.03), while the fry effect was similar between the sexes. The heritability of males (SL=0.25; BD=0.3; BW=0.33; BA=0.31; BV=0.35) was, in general, higher than those present in females (SL=0.19; BD=0.2, BW=0.18, BA=0.2; BV=0.2), and the genetic correlations between males and females were below 0.5 (SL=0.5; BD=0.39, BW=0.42, BA=0.45; BV=0.43). Thus, it can be seen that the males respond differently to the females in terms of body shape, of the selection for weight gain.
Keywords: Bayesian inference; genetic correlation; GIFT tilapia; heritability; male and female